Effect of Factor H on Complement Alternative Pathway Activation in Human Serum Remains on Porcine Cells Lacking N-Glycolylneuraminic Acid - Lee, Haneulnari; Park, Eun Mi; Ko, Nayoung; Choi, Kimyung; Oh, Keon Bong; Kang, Hee Jung (Frontiers in Immunology, 2022)
Background: Triple knockout (TKO) donor pigs lacking alpha-1,3-galactose (Gal), N-glycolylneuraminic acid (Neu5Gc), and Sd(a) expressions were developed to improve the clinical success of xenotransplantation. Neu5Gc, a sialic acid expressed on cell surfaces, recruits factor H to protect cells from attack by the complement system. Lack of Neu5Gc expression may cause unwanted complement activation, abrogating the potential benefit of gene-modified donor pigs. To investigate whether TKO porcine cells display increased susceptibility to complement activation in human serum, pathway-specific complement activation, apoptosis, and human platelet aggregation by porcine cells were compared between alpha-1,3-galactosyltransferase gene-knockout (GTKO) and TKO porcine cells. Methods: Primary porcine peripheral blood mononuclear cells (pPBMCs) and endothelial cells (pECs) from GTKO and TKO pigs were used. Cells were incubated in human serum diluted in gelatin veronal buffer (GVB++) or Mg++-EGTA GVB, and C3 deposition and apoptotic changes in these cells were measured by flow cytometry. C3 deposition levels were also measured after incubating these cells in 10% human serum supplemented with human factor H. Platelet aggregation in human platelet-rich plasma containing GTKO or TKO pECs was analyzed. Results: The C3 deposition level in GTKO pPBMCs or pECs in GVB++ was significantly higher than that of TKO pPBMCs or pECs, respectively, but C3 deposition levels in Mg++-EGTA-GVB were comparable between them. The addition of factor H into the porcine cell suspension in 10% serum in Mg++ -EGTA-GVB inhibited C3 deposition in a dose-dependent manner, and the extent of inhibition by factor H was similar between GTKO and TKO porcine cells. The percentage of late apoptotic cells in porcine cell suspension in GVB++ increased with the addition of human serum, of which the net increase was significantly less in TKO pPBMCs than in GTKO pPBMCs. Finally, the lag time of platelet aggregation in recalcified human plasma was significantly prolonged in the presence of TKO pECs compared to that in the presence of GTKO pECs. Conclusion: TKO genetic modification protects porcine cells from serum-induced complement activation and apoptotic changes, and delays recalcification-induced human platelet aggregation. It does not hamper factor H recruitment on cell surfaces, allowing the suppression of alternative complement pathway activation.